Costimulatory Pathways in Lymphocyte Proliferation Induced by the Simian Immunodeficiency Virus SIVsmmPBj14 - Whetter, Linda (American Society for Microbiology, 1998)
The PBj14 isolate of the simian immunodeficiency virus SIVsmmPBj14 is unique among primate lentiviruses in its ability to induce lymphocyte proliferation and acutely lethal disease. The studies reported here show that viral induction of T-cell proliferation requires accessory cells, such as primary monocytes or Raji B-lymphoma cells, as well as the presence of a putative immunoreceptor tyrosine-based activation motif within the viral Nef protein. Addition of CTLA4-immunoglobulin fusion protein or anti-B7 antibodies to virally infected T cells led to substantial, but not complete, inhibition of monocyte-costimulated T-cell proliferation—suggesting that both CD28/B7-dependent and non-CD28-dependent pathways may contribute to the costimulation of virally induced lymphoproliferation. Finally, cyclosporin A, a specific inhibitor of the calcium-calmodulin-regulated phosphatase activity of calcineurin, which influences activation of the transcription factor nuclear factor of activated T cells, was shown to block virally mediated T-cell proliferation. Taken together, these findings suggest that the effect of SIVsmmPBj14 on T-cell activation may be functionally analogous, at least in part, to the effect of engagement of the T-cell receptor.